ANALISIS PROBLEMATIKA ORANGTUA DI BEBERAPA NEGARA DALAM MENDAMPINGI ANAK BELAJAR DI MASA PANDEMI COVID-19 - Bayu Fitra Prisuna (PSGA LP2M IAIN Pontianak, 2021)
This research is a literature study with a qualitative approach that aims to analyze similarities related to the problems of parents in several countries in assisting children to study during a pandemic. In this study, the author uses various written sources from scientific articles originating from national and international journals as well as documents that are considered relevant to the study in this research. The results showed that the problems experienced by parents in several countries in assisting children to study during the COVID-19 pandemic have in common, namely difficulties in growing motivation in children so that they can carry out learning well in order to achieve learning goals